Intertextual Realms: Towards a Chronotopic Model of Intertextuality (Altre Modernità, 2017)
Since the 1966 publication of Jean Rhys's Wide Sargasso Sea, it has become a literary fashion to re-imagine well-known, and often canonical, fictional texts from the perspective of 'the minor,' a character whose marginalized existence within the literary classic tends to reflect relations of power and privilege in the extra-fictional realm.